The Effect of Product Design and Price Discount on Impulse Buying through Positive Emotion as a Mediating Variable in the Fast Fashion Industry: Uniqlo in Jakarta - Raisya Rahma Aulia; Sari Listyorini (UNIVED Press, 2026)
This study analyzes the effect of product design and price discount on impulse buying through positive emotion as a mediating variable among Uniqlo consumers in Jakarta. A quantitative approach was used with data from 130 respondents and analyzed using Structural Equation Modeling (SEM). The results show that product design has a positive and significant effect on impulse buying and positive emotion. Price discount has no significant direct effect on impulse buying but has a positive effect on positive emotion. Positive emotion also has a positive and significant effect on impulse buying. The mediation analysis indicates that positive emotion partially mediates the relationship between product design and impulse buying, and fully mediates the relationship between price discount and impulse buying. Overall, the findings highlight that emotional factors and product design play a more dominant role than price discounts in driving impulse buying behavior.